Mapping the reactivity of the quinoline ring-system – Synthesis of the tetracyclic ring-system of isocryptolepine and regioisomers. Issue 21 (24th May 2019) - Håheim, Katja S.; Urdal Helgeland, Ida T.; Lindbäck, Emil; Sydnes, Magne O.
Abstract: Bromoquinolines (2-bromoquinoline – 8-bromoquinoline and 5-bromo-3-methoxyquinoline) and 2-aminophenylboronic acid hydrochloride were subjected to Suzuki-Miyaura cross-coupling conditions resulting in formation of the desired biaryl systems in good yields. The resulting biaryls were then subjected to palladium catalyzed CH activation/CN bond formation utilizing PdCl2 (dppf). The reactions revealed large differences in reactivity depending on the attachment point for the 2-aminophenyl group on the quinoline. The variation in the reactivity was rationalized based on the electron distribution around the quinoline ring-system. Graphical abstract: Image 1